STUDY OF THE EFFECT OF SOME ALKALOIDS ON THE CONTRACTILE ACTIVITY OF AORTIC SMOOTH MUSCLE CELLS - Mirzayeva Yulduzkhon Takhirjonovna (Scholar Express Journals, 2024)
The aim of the work was to study the effect of 1-O-acetylkarakoline, a derivative of the diterpenoid alkaloid karakolin, isolated from the plant Aconitum karakolicum, on the contractile activity of smooth muscle cells (SMC) of the rat aorta. Karakolin has a pronounced antiarrhythmic effect, which is determined by the presence of specific functionally important groups in its structure [3]. Thus, the replacement of the OH-group at the carbon atom C-1 of the lycoketonin skeleton of Karakolin with an acetyl group (Fig. 1) leads to a significant increase in antiarrhythmic activity of 1-O-acetylkarakoline
Keywords: smooth muscle; sarcoplasmic reticulum; aorta; phenylephrine